Vitrification of canine ovarian tissue using the Ovarian Tissue Cryosystem (OTC) device. Issue 8 (14th July 2021) - Brandão, Fabiana Aparecida Santilli; Alves, Kele Amaral; de Brito, Danielle Cristina Calado; Pereira, Leda Maria Costa; de Morais, Glayciane Bezerra; Ñaupas, Lucy Vanessa Sulca; de Souza, Samara Silva; Alves, Benner Geraldo; Rodrigues, Ana Paula Ribeiro; Teixeira, Dárcio Ítalo Alves
Abstract: The present study evaluated the effect of Ovarian Tissue Cryosystem (OTC) on follicular morphology and density, as well as on stromal cell density of vitrified canine ovarian tissue. Canine ovarian fragments collected from adult female dogs in stages of the random oestrous cycle were fixed (FC, fresh control) or vitrified (VIT) with an OTC device. After vitrification and warming, the fragments were fixed for histological analysis. Overall, the mean percentage of normal pre‐antral follicles decreased after vitrification procedure (FC: 74.5% ± 1.6% vs. VIT: 52.05% ± 1.5%). Although the rates of normal primordial (71.1% ± 1.8%) and secondary (0.7% ± 0.4%) follicles vitrified showed a reduction ( p  < .05), vitrification using OTC showed considerable preservation of follicles, when compared to the fresh control (81.1% ± 1.5% and 2.3% ± 0.6%, respectively). The mean follicular density was maintained after vitrification (FC: 199.65 ± 12.8 vs. VIT: 199.68 ± 10.8), whereas the stromal cell density decreased in the VIT group. Based on the results, we recommend the use of OTC for vitrification of canine ovarian tissue.